Floristic Diversity of Bhadra Wildlife Sanctuary in the Central Western Ghats Region, Karnataka - Krishnamurthy, Y. L.; Prakasha, H. M.; Nanda, A. (Indian Forester, 2009)
An extensive survey of the angiospermic floristic diversity was carried out in Bhadra Wildlife Sanctuary, Karnataka. A total of 30 transect each measuring 250 m Ã— 4 m (0.1 ha) were laid randomly at different geographic locations of the sanctuary and plants were enumerated. The enumeration, carried out in the transects resulted in a total of 406 species, 294 genera belonging to 98 families. Of these enumerated plant species, 169 were tree forms, 37 shrubs, 82 herbs, 70 climbers and remaining were miscellaneous category. Xylia xylocarpa form the denser species among the trees in the sanctuary with a total of 614 trees/ 30 transects (D= 20.47 trees/transect) while Ichnocarpus frutescens (76 individuals, D=2.53) and Stachytarpeta indica (79 individuals, D= 2.63) were dominant among climbers and herbs respectively. The study also recorded a very good Shannon -Wiener and Simpson diversity index of 3.4 and 16.84 for trees, 3.57, 26.14 for climbers and 3.9, 40.2 for herbs. Twelve species among these were designated under endangered threat category while 56 were remarked as endemic to Western Ghats and 106 species as rare. Over 234 plant species were commonly distributed in the sanctuary.